On the Virtue-theoretic Approach to Argument Appraisal - McKeon, Matthew (Informal Logic)

(untitled) (Informal Logic, 2024)
Two criticisms of the virtue-theoretic approach to argument appraisal are as follows. First, it is inadequate as argument cogency is conceptually independent of the characteristics of arguers (Bowell and Kingsbury 2013). Second, it is unmotivated since the viability of virtue argumentation theory (VAT) doesn’t require a virtue-theoretic approach to argument appraisal. This deflates the first criticism as an evaluation of VAT (Gascon 2016, Paglieri 2015). I consider each and explain why it is misguided highlighting the connection between the general concept of good argument and associated criteria of goodness, and the connection between good arguments and good arguing.